Characterization of calbindin D28k expressing interneurons in the ventral horn of the mouse spinal cord. Issue 1 (15th November 2017) - Floyd, Taylor L.; Dai, Yiyun; Ladle, David R.
Abstract : Background : Expression of the calcium binding protein, calbindin (CB), is well established as a hallmark of Renshaw cells, a class of interneurons found in spatially restricted areas in the ventral spinal cord that directly modulate motor neuron activity. CB expression, however, is not restricted only to Renshaw cells in the ventral horn, and within this population other interneuron subtypes may be identifiable on the basis of cell position and the potential for coexpression of other calcium binding proteins.Results : Here we have quantified the changing CB expression pattern in the ventral spinal cord across postnatal development in the mouse. Fewer neurons express CB as postnatal development progresses, and those neurons frequently coexpress other calcium binding proteins (calretinin and parvalbumin) in subpopulations with distinct spatial distributions. We also found a significant portion of CB‐expressing interneurons receive putative synaptic contacts from primary sensory afferents.Conclusions : These findings suggest CB labels a heterogeneous group of interneurons in the ventral horn, some of which may process sensory information. Based on cellular position, CB expression may be a shared feature of subsets of interneurons arising from multiple ventral progenitor domains. Developmental Dynamics 247:185–193, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Fewer neurons in the ventral spinal cord express calbindin as postnatal development progresses. Calbindin neurons frequently coexpress other calcium binding proteins (calretinin and parvalbumin) in subpopulations with distinct spatial distributions. A significant portion of calbindin‐expressing interneurons receive putative synaptic contacts from primary sensory afferents.